“What’s the Use?”: Undoing, Decolonizing, Liberating, and Righting Literacies Assessment in Turbulent Times - Honeyford, Michelle; Watt, Jennifer (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
This conceptual paper extends the Re-imagining Literacies Assessment knowledge mobilization project and its goals of undoing, decolonizing, liberating, and righting assessment, explored through examples of assessment-in-use in classrooms with young children, a Cree language immersion program, anti-racist writing pedagogy, and research in reading instruction and assessment. In conversation with one another, three assemblings of stories, relations, complications, and questions are presented, drawing attention to assessment in relation to noticing, positioning, and dis/re/connecting. Undoing, decolonizing, liberating, and righting become concepts to use in thinking through the use of assessment and in proposing urgent and emergent questions, practices, and possibilities for students and teachers.